Development of Surodadi Tourism Village as a Form of Strengthening the Community’s Economy - Lany Christanty; Barkah Susanto; Nia Kurniati Bachtiar; Laili Qomariyah; Afla Azzahra Putri; Lasiona Ravi Nirwana (LPPMPK-Sekolah Tinggi Teknologi Muhammadiyah Cileungsi, 2023)
Surodadi Village, Candimulyo District, Magelang Regency is located in a mountainous area, more precisely the Gandu National Park area. The tourist attraction in this village is the pine forest which presents beautiful and soothing natural beauty. However, local people do not realize the potential around it can become a tourist destination that attracts many visitors. This community service aims to build a tourist village in Surodadi. However, along the way, other problems were discovered, namely the not yet formed Bumdes and Pokdarwis, even though their roles are very important in the management of tourism villages in the future. The problem solving methods are Forum Group Discussion (FGD), outreach, training, and mentoring. The result is the establishment of the Surodadi tourist village as well as the establishment of Bumdes and Pokdarwis which manage it both in administration and operations.